Penerapan Media Puzzle Dalam Peningkatan Interaksi Anatara Guru Dan Peserta Didik Di SDN Kepanjen 1 Jombang - Lailiya, Nirmala Rahmatul; Raharjo, Resdianto Permata (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2024)
The aim of this research is to describe the interactions between teachers and students that occur in science and science learning in class IV at SDN Kepanjen 1 Jombang using Puzzle Media. The approach used is a qualitative approach with descriptive methods. The research subjects were teachers and students in class IV of SDN Kepanjen 1 Jombang. The object of research is the interaction of teachers and students in science and science learning. The application of puzzle media to improve the psychomotor skills of class IV students at SDN Kepanjen 1 Jombang is based on the fact that students are not enthusiastic and feel bored during the learning process because the learning process only uses lecture methods and learning media which are still less interesting. So there is a need for learning media to create conducive and enjoyable learning in science learning regarding Plants, the Source of Life on Earth. Data collection techniques used by researchers are questionnaires and observations, which are techniques to help researchers. Analysis techniques to determine the interpretation of data that has been collected from previous research results. Apart from that, the data collected was then analyzed using descriptive qualitative methods, namely describing and presenting it clearly and easily to understand. The results of the research explain that during the science lesson on Plants, the Source of Life on Earth, class IV at SDN Kepanjen 1 Jombang, there was still a lack of interaction during the learning process by overcoming problems assisted by learning media. The researcher used Puzzle media as a means for interaction. When the media is applied it produces good interaction because of the students' interest in the media used. Thus, puzzle media to increase interaction between teachers and fourth grade elementary school students is suitable for use in learning.